Short-term weight gain among preschool children in rural Burkina Faso: a secondary analysis of a randomised controlled trial. Issue 7 (29th July 2019) - Dennis, Elena G; Sie, Ali; Ouermi, Lucienne; Dah, Clarisse; Tapsoba, Charlemagne; Zabre, Pascal; Bärnighausen, Till; O'Brien, Kieran S; Lebas, Elodie; Keenan, Jeremy D; Oldenburg, Catherine E
Abstract : Objectives: Nutrition has profound effects on children's health outcomes and is linked to weight gain and cognitive development. We used data from a randomised controlled trial to evaluate the prospective associations between dietary, socioeconomic and demographic factors and short-term weight gain during the lean season in a rural area of Burkina Faso. Design: Prospective cohort data arising from a randomised controlled trial of the effect of antibiotic distribution on child growth and intestinal microbial diversity. Setting: Two rural communities in Nouna District, Burkina Faso. Participants: 246 children aged 6–59 months living in the study communities were enrolled in the study. Primary and secondary outcome measures: Anthropometric measurements, including weight and height, were obtained at baseline and 1 month. Results: Of 246 children, the median weight for wasted children at baseline (weight-for-height z-score <−2) was 9.7 kg (IQR 8.65–10.8) and the weight of non-wasted children was 12.8 kg (IQR 10.9–14.75). Food insecurity was significantly associated with decreased weight gain velocity (mean difference −0.03 g/kg/day, 95% CI −0.06 to −0.006, p=0.04). Conclusion: Experiences of household food insecurity before the beginning of the lean season were associated with decreased weight gain in children in rural Burkina Faso during the lean season, although the mean difference was small. Understanding the relationship between timing of food insecurity and anthropometric outcomes may help to develop policies and health programme that address both of these issues. Trial registration number: NCT03187834 .